Хархорины бүсийн цүүгэл формацын хурдас хуримтлалын насны асуудалд - Д., Эрдэнэчимэг; Т., Оюунчимэг; Д., Шарав (Geological Issues, 2022)
This study presents the depositional age and provenance of the Tsuugel formation sedimentary rocks based on detrital zircon geochemistry and U-Pb geochronological analyses. The Tsuugel formation consists of bluish-gray, greenish-gray colored fine-medium grained sandstones, dark-gray, bluish-gray siltstone, and gravelites. The bluish-grey sandstone (Kh-19-74) of the Tsuugel formation where collected south of the Khukh suuj river and north-western of the Khuut mountain was selected for U-Pb geochronological analyses. Totally, 110 zircon grains were analyzed, and 97 zircons have highly concordant ages ranging between 1032 ± 24 and 301 ± 6 Ma. The youngest 10 zircon grains yield a weighted mean age of 309.7 ± 4.1Ma. The chondrite-normalized REE diagram shows 2 distinct patterns which are magmatic and hydrothermal zircon. Magmatic zircons have low light REE, high heavy REE content, (Sm/La)N = 44.9-925.8 (av. 265.7), Ce/Ce* = 18.1-129.6 (av. 67.5) its indicated unaltered magmatic source in continental crust rock, and have higher abundance of the REE, flatter light REE patterns, (Sm/La)N = 0.49-1.77 (av.0.85), Ce/Ce* = 0.99-1.69 (av. 1.32) described for hydrothermal-altered zircon.